Measuring Americans' Support for Adapting to 'Climate Change' or 'Extreme Weather'. Issue 5 (4th July 2022) - Carman, Jennifer P.; Lacroix, Karine; Goldberg, Matthew H.; Rosenthal, Seth; Gustafson, Abel; Howe, Peter; Marlon, Jennifer; Leiserowitz, Anthony
ABSTRACT: Climate communicators can use the terms 'climate change' or 'extreme weather' to describe climate change adaptation strategies. However, the terms might differentially affect individuals' support for those strategies. We examined Americans' ( N = 1, 558) endorsement of climate change adaptation behaviors and policies based on whether they were described using 'climate change' or 'extreme weather.' Republicans' endorsement of some adaptation behaviors and policies was lower when using the term 'climate change' compared with 'extreme weather, ' while in contrast, Democrats' reported willingness to engage in collective adaptation behaviors and support for policies related to protecting natural spaces was higher when using the term 'climate change.' The appropriateness of using 'climate change' or 'extreme weather' is situational depending on both the audience and the behaviors and policies being communicated.